Síndrome del cuidador en cuidadores familiares de adolescentes y adultos con trastornos del neurodesarrollo en la fundación red promotora de capacidades (2018)
The purpose of this thesis is to analyze the level of overload caused by the impact of caring for young adults with neurodevelopmental disorders. Where caring for these people with dependency implies responsibility functions and physical, psychological and social care actions due to these tasks, it is possible that the caregiver's work develops the caregiver syndrome, due to assuming the role of care, it is a quantitative descriptive study with a scientific positivist approach. For the evaluation process, the Zarit Overload Scale was applied to 30 caregivers of the Promoting Capacity Red Foundation, in the town of Usme in the city of Bogotá, among the characteristics of the sample was a distribution of caregivers of 23 women and 7 men in ages between 20 and 65 years. The evaluation process indicated that 33% of the people evaluated do not present an overload, 57% have a light overload level and 10% suffer from an intense overload.